Analisis Arus Kas Terhadap Return Saham Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Di Bursa Efek Indonesia - NURCHAYATI NURCHAYATI; SAYIDATIN NASAROH (Serat Acitya, 2017)
This study aims to determine the effect of cash flow (operating cash flow, cash flow financing and investing cash flows)  to return stock in companies manufacturing food and beverage sector in the Indonesia Stock Exchange (BEI) Year 2014-2016 The data used is secondary data obtained through purposive sampling method of sampling is based on subjective considerations researchers adjusted for the purpose of research. A total of 11 companies selected as samples so that the total data for 3 years gained as much as 33 data.The analysis technique used is multiple linear regression with the result that the variable operating cash flow, cash flow financing and investing cash flow positive and significant effect on stock returns in companies manufacturing food and beverage sector in the Indonesia Stock Exchange (BEI) Year 2014-2016 either partially or simultaneously. The most influential independent variable is the operating cash flow.Advice can be given to investors is to pay attention to cash flow (operating cash flow, cash flow financing and investing cash flows)  of a company before deciding to invest. Keywords: Return Share, Operating Cash Flow, Cash Flow Investments, Cash Flow Financing